Statin therapy is associated with the development of new‐onset diabetes after transplantation in liver recipients with high fasting plasma glucose levels. Issue 5 (25th February 2014) - Cho, Yongin; Lee, Min Jung; Choe, Eun Yeong; Jung, Chang Hee; Joo, Dong Jin; Kim, Myoung Soo; Cha, Bong Soo; Park, Joong‐Yeol; Kang, Eun Seok
<x xml:space="preserve">Abstract</x> New‐onset diabetes after transplantation (NODAT) and dyslipidemia are important metabolic complications after liver transplantation (LT) that can adversely affect both allograft and patient survival. Statins are used as first‐line therapies for dyslipidemia because of their effectiveness and safety profile. However, it has recently been reported that statin therapy is associated with new‐onset diabetes in the nontransplant population. The aim of this study was to investigate the association between statin therapy and the development of NODAT in LT recipients. Three hundred sixty‐four LT recipients who underwent transplantation between the ages of 20 and 75 years without a previous history of diabetes were enrolled in this study. We evaluated the incidence of NODAT with respect to statin use as well as other risk factors. The incidence of NODAT was significantly higher in the statin group (31.7%) versus the control group (17.6%, P = 0.03). The mean follow‐up period was 37.8 ± 19.0 months for the statin group and 42.7 ± 16.0 months for the control group (P = 0.07). Statin use was significantly associated with NODAT development after adjustments for other risk factors [hazard ratio (HR) = 2.32, 95% confidence interval (CI) = 1.23‐4.39, P = 0.01]. Impaired fasting glucose before transplantation was also a risk factor for NODAT development (HR = 2.21, 95% CI = 1.36‐3.62, P = 0.001). There were no significant differences in age, body mass index, cumulative corticosteroid dose, or fasting plasma glucose (FPG) levels between the groups. Patients with high FPG levels were more likely to develop NODAT when they were placed on statins after LT (P = 0.002). In conclusion, statin treatment could contribute to the development of NODAT in LT recipients, especially if they have high baseline FPG levels. Liver Transpl 20:557–563, 2014. © 2014 AASLD.